Floristic Inventory of Invasive Alien Aquatic Plants Found in Malebo Pool in Congo Rivers, Kinshasa, DR. Congo (Case of MOLONDO, MIPONGO, and JAPON Islands) (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: invasive alien plants; environmental impacts; pool malebo; kinshasa; DR congo